Determination of copper, cadmium and zinc in Abelmoschus esculentus L. Moench using flame atomic absorption spectrophotometry - Mohd. Haziq Assadiq Abd. Razak, 1994-, author; Razali Ismail, 1960-, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Industri Kimia)) - Universiti Teknologi Malaysia, 2017